ANALISIS KINERJA KEUANGAN KOPERASI PEGAWAI XYZ - Siti Nur Azizah; Alfiani Hana Putri, Aswin Saputra, Aulia Oktaviani, Gea Amanda (Prosiding Seminar Nasional Indonesia, 2024)
Cooperatives are non-bank financial institutions that help their members and the community to improve their standard of living. This quantitative descriptive study intends to analyze the financial performance of the XYZ Employee Cooperative for the 2020-2022 period with a sample, namely financial statement data for 2020-2022. The analytical method utilized is financial ratio analysis, encompassing liquidity, profitability, and solvency metrics. According to industry standards, the current ratio and cash ratio liquidity ratios rank well. The solvency ratio, debt-to-equity ratio, and debt-to-assets ratio all indicate positive outcomes by industry standards. Different results are shown in the return on equity profitability ratio because it is close to the maximum value set by industry standards. Other profitability ratios such as return on assets show good results according to industry standards as well as net profit margin and gross profit margin which show good results.